Magnetic resonance imaging in early rheumatoid arthritis: a multicenter, prospective study. Issue 2 (February 2016) - Li, Ru; Liu, Xia; Ye, Hua; Yao, Hai-Hong; Guo, Jia-Long; Li, Guang-Tao; Li, Xing-Fu; Xue, Yu; Zhao, Jin-Xia; Gu, Fei; Zou, Qing-Hua; Chen, Li-Na; et al.
Abstract To identify the magnetic resonance imaging (MRI) features of hands and wrists in early rheumatoid arthritis (RA). A total of 129 early arthritis patients (≤1 year) were enrolled in the study. At presentation, MRI of the hands was performed, with clinical and laboratory analyses. After a 1-year follow-up, clinical diagnosis of early RA or non-RA was confirmed by two rheumatologists. The characteristics of MRI variables at baseline in RA patients not fulfilling ACR 1987 criteria [RA-87(−)] were compared with those fulfilling ACR1987 criteria [RA-87(+)] and non-RA. In the 129 early arthritis patients, 90 were diagnosed with RA in a 1-year follow-up. There were 47.8 % (43/90) of the RA patients not fulfilling ACR 1987 criteria [RA-87(−)]. The scores of synovitis in RA-87(−) patients were similar with those in RA-87(+) [Synovitis score, 14.0 (IQR, 4.0–25.0) vs. 14.0 (IQR, 10.0–25.0), p > 0.05]. Compared with those in non-RA, RA-87(−) patients had higher synovitis scores and occurrence of synovitis in proximal interphalangeal (PIP) joints [synovitis score, 14.0 (IQR, 4.0–25.0) vs. 6.0 (IQR, 2.0–14.5), p = 0.046; occurrence of PIP synovitis: 53.5 vs. 27.3 %, p = 0.02]. There was no significant difference of bone marrow edema, bone erosion, and tenosynovitis between RA-87(−) and non-RA. Synovitis in PIP joints was independent predictor for RA-87(−) [OR, 3.1 (95 %CI 1.2–8.1)]. High synovitis scores and synovitis in PIP joints on MRI were important in early RA, especially those not fulfilling ACR 1987 criteria.